Avaliação dos efeitos antibacterianos do composto 6h,12h-dibenzo[b,f][1,5]dioxocina-6,12-diona sobre linhagens de pseudomonas aeruginosa - Pereira, Rosângela Targino (2024)
The genus Pseudomonas encompasses a series of microorganisms whose strong characteristic is their opportunism to infection. Pseudomona aeruginosa, a bacterium belonging to this group, is a pathogenic microorganism with high infection rates, especially in hospital settings, as well as being associated with a high level of morbidity and mortality. Based on all these concerns about P. aeruginosa resistance factors in relation to clinical treatments and inhibition of biofilm activity, researchers are looking for new alternatives through new compounds or the association of chemical elements capable of enhancing pharmaceuticals for antibacterial purposes. The main objective of this research is to evaluate the antimicrobial capacity of the molecule 6H,12H-Dibenzo[b,f][1,5]dioxocin-6,12-dione on Pseudomonas aeruginosa strains by in vitro assays. The protocols were developed at the Laboratory of Environmental Microbiology (LAMA), Department of Biotechnology (DB), Biotechnology Center (CBiotec), Federal University of Paraíba. P. aeuruginosa ATCC-25873 was used for the bench tests. The minimum inhibitory concentration (MIC) was 10-17M, from serial micro dilutions from 10-2 to 10-17M, the latter being the lowest concentration in the wells with bacteriostatic activity. It should also be noted that the experiment was performed in triplicate (n=3) and the plates were analyzed at 24 hours. The MBC corroborated the results shown in the MIC so it is concluded through the development of this research that the synthesized molecule, Dibenzo, showed significant and promising antimicrobial results, with efficient lytic activity, acting on the cell wall of the pathogen.